On the Number of Real Zeros of a Certain Kind of Polynomials - Diko Souroujon; Teodora Zapryanova (Research and Applications Towards Mathematics and Computer Science Vol. 9, 2024)
In the present paper we consider the polynomials of the type qn (x) = (x+1)n P (x)+xn Q (x), where P (x) and Q(x) are nonconstant polynomials with real coefficients of degree m such that \(_x→±∞P(x)Q(x)\) is a finite positive number. We investigate the number of real zeros of qn(x) when \(n→∞\).